THE PROBLEM OF LINGUISTIC TAGGING OF LINGUISTIC UNITS IN A PARALLEL CORPUS (Scientific journal of the Fergana State University, 2025)
In the article, in the translation of Chingiz Aitmatov's novel "Plakha" into Uzbek, the linguistic and cultural units recreated by the metaphor method are analyzed in a parallel corpus. The analyzed linguistic and cultural units are annotated based on the Turkish language tagging system. In the article, the differences in sentence constructions that appear in the process of converting from the source language to the target language are shown in a table based on SmartCat technology. Also, an opinion is expressed about the composition of alternative and non-alternative stable compounds in the translation.